A New Tetracycline for Acne: The Role of Sarecycline - Witkowska, Antonina; Zapalska, Barbara Anna; Piotrowska, Julia; Witkowska, Adrianna; Domańska, Adrianna; Łubińska-Kowalska , Aleksandra; Żak-Gontarz, Agata; Minda, Aleksandra; Janikowska, Justyna; Długosz, Krzysztof Julian; et al. (Quality in Sport, 2025)
INTRODUCTION AND OBJECTIVE A common dermatological disorder that significantly affects both the physical appearance and mental well-being of patients is acne vulgaris. Its presence is frequently associated with reduced quality of life due to its chronic nature, visible lesions, and the risk of permanent scarring. The pathogenesis of acne is multifactorial and includes follicular hyperkeratinization, colonization of the skin by Cutibacterium acnes, inflammation, and overproduction of sebum. The purpose of this article is to present sarecycline, a third-generation tetracycline antibiotic approved by the United States Food and Drug Administration in 2018 for the treatment of moderate to severe acne vulgaris. The review summarizes current scientific findings regarding its clinical efficacy and safety profile. MATERIALS AND METHODS This article is based on a literature review concerning the therapeutic application of sarecycline in acne vulgaris. A comprehensive search was conducted using scientific databases including PubMed and Google Scholar, covering the period from 1999 to 2024. Keywords such as acne, tetracycline, and sarecycline were used to identify relevant studies. CONCLUSION Compared to traditional tetracyclines, sarecycline demonstrates limited activity against Gram-negative bacteria, which helps reduce the incidence of gastrointestinal side effects. Due to its favorable efficacy and safety profile, it is considered a valuable treatment option, especially for patients requiring long-term antibiotic therapy. Sarecycline has the potential to redefine established treatment paradigms in the management of acne vulgaris.